Erratum: Biomarker-guided clinical decisions: For patients, health economists or neither? (European Respiratory Journal (2013) 42 (895-897)) - Robinson, P.; Latzin, P.; Verbanck, S.; Hall, Graham; Horsley, A.; Gappa, M.; Thamrin, C.; Arets, H.; Aurora, P.; Fuchs, S.; King, G.; Lum, S.; et al. (European Respiratory Society, 2013)
Unfortunately, the affiliation details for the author were published incorrectly in the above article. The correct affiliation details are as follows.